Safety and efficacy of co-careldopa as an add-on therapy to occupational and physical therapy in patients after stroke (DARS): a randomised, double-blind, placebo-controlled trial. Issue 6 (June 2019) - Ford, Gary A; Bhakta, Bipin B; Cozens, Alastair; Hartley, Suzanne; Holloway, Ivana; Meads, David; Pearn, John; Ruddock, Sharon; Sackley, Catherine M; Saloniki, Eirini-Christina; Santorelli, Gillian; Walker, Marion F; et al.
Summary: Background: Dopamine is a key modulator of striatal function and learning and might improve motor recovery after stroke. Previous small trials of dopamine agonists after stroke provide equivocal evidence of effectiveness on improving motor recovery. We aimed to assess the safety and efficacy of co-careldopa plus routine occupational and physical therapy during early rehabilitation after stroke. Methods: This double-blind, multicentre, randomised controlled trial of co-careldopa versus placebo in addition to routine NHS occupational and physical therapy was done at 51 UK NHS acute inpatient stroke rehabilitation services. We recruited patients with new or recurrent clinically diagnosed ischaemic or haemorrhagic (excluding subarachnoid haemorrhage) stroke 5–42 days before randomisation, who were unable to walk 10 m or more, had a score of less than 7 points on the Rivermead Mobility Index, were expected to need rehabilitation, and were able to access rehabilitation after discharge from hospital. Participants were assigned (1:1) using stratified random blocks to receive 6 weeks of oral co-careldopa or matched placebo in addition to routine NHS physiotherapy and occupational therapy. The initial two doses of co-careldopa were 62·5 mg (50 mg of levodopa and 12·5 mg of carbidopa) and the remaining doses were 125 mg (100 mg of levodopa and 25 mg of carbidopa). Participants were required to take a single oral tablet 45–60 min before physiotherapy or occupational therapy session. The primary outcome was ability to walk independently, defined as a Rivermead Mobility Index score of 7 or more, at 8 weeks. Primary and safety analyses were done in the intention-to-treat population. The trial is registered on the ISRCTN registry, number ISRCTN99643613. Findings: Between May 30, 2011, and March 28, 2014, of 1574 patients found eligible, 593 (mean age 68·5 years) were randomly assigned to either the co-careldopa group (n=308) or to the placebo group (n=285), on an average 18 days after stroke onset. Primary outcome data were available for all 593 patients. We found no evidence that the ability to walk independently improved with co-careldopa (125 [41%] of 308 patients) compared with placebo (127 [45%] of 285 patients; odds ratio 0·78 [95% CI 0·53–1·15]) at 8 weeks. Mortality at 12 months did not differ between the two groups (22 [7%] vs 17 [6%]). Serious adverse events were largely similar between groups. Vomiting during therapy sessions, after taking the study drug, was the most frequent adverse event and was more frequent in the co-careldopa group than the placebo group (19 [6·2%] vs 9 [3·2%]). Interpretation: Co-careldopa in addition to routine occupational and physical therapy does not seem to improve walking after stroke. Further research might identify subgroups of patients with stroke who could benefit from dopaminergic therapy at different doses or times after stroke with more intensive motor therapy. Funding: Medical Research Council.